A strategy for OCT estimation of the optic nerve head pigment epithelium central limit‐inner limit of the retina minimal distance, PIMD‐2π. Issue 2 (10th September 2018) - Sandberg Melin, Camilla; Malmberg, Filip; Söderberg, Per G.
Abstract: Purpose: To develop a semi‐automatic algorithm for estimation of pigment epithelium central limit‐inner limit of the retina minimal distance averaged over 2 π  radians (PIMD‐2 π ) and to estimate the precision of the algorithm. Further, the variances in estimates of PIMD‐2 π were to be estimated in a pilot sample of glaucomatous eyes. Methods: Three‐dimensional cubes of the optic nerve head (ONH) were captured with a commercial SD‐OCT device. Raw cube data were exported for semi‐automatic segmentation. The inner limit of the retina was automatically detected. Custom software aided the delineation of the ONH pigment epithelium central limit resolved in 500 evenly distributed radii. Sources of variation in PIMD estimates were analysed with an analysis of variance. Results: The estimated variance for segmentations and angles was 130  μ m 2 and 1280  μ m 2, respectively. Considering averaging eight segmentations, a 95 % confidence interval for mean PIMD‐2 π was estimated to 212 ± 10  μ m (df = 7). The coefficient of variation for segmentation was estimated at 0.05. In the glaucomatous eyes, the within‐subject variance for captured volumes and for segmentations within volumes was 10  μ m 2 and 50  μ m 2, respectively. Conclusion: The developed semi‐automatic algorithm enables estimation of PIMD‐2 π in glaucomatous eyes with relevant precision using few segmentations of each captured volume.